Human resources as a strategic enabler of circular economy adoption: a bibliometric and thematic analysis - Menshikova, Maria; Plotnic, Olesea; Tambovceva, Tatjana (Serbian Journal of Management, 2025)
This paper presents a comprehensive bibliometric and thematic analysis of 313 peer-reviewed articles indexed in Scopus, mapping the intersection between circular economy (CE) and human resources (HR). The study confirms the central role of HR in enabling the adoption and diffusion of CE practices across industries and regions. Our findings highlight that the success of CE initiatives depends not only on technological advancements and structural changes but critically on the preparedness, engagement, and well-being of the workforce. Key HR practices-including skill development, leadership cultivation, digital and virtual training, and inclusive talent management-are shown to be vital for equipping employees with the capabilities needed to implement circular strategies. The analysis reveals the growing importance of integrating digital technologies, such as Industry 4.0 tools, with human capital development, while also emphasizing the need for supportive working conditions, including safe, fair, and inclusive workplaces, to stimulate sustainable behaviors. The study identifies 15 thematic clusters and highlights emerging topics such as digital circular economy, circular entrepreneurship, and decent work. This paper contributes to understanding the strategic role of HRM in circular transitions and suggests directions for future research on contextual factors, digital readiness, and HR’s role in advancing circular business models globally.
Keywords: circular economy; human resource management; skills; training; engagement